Enterococcus faecium NCIMB 10415 Modulates Epithelial Integrity, Heat Shock Protein, and Proinflammatory Cytokine Response in Intestinal Cells - Shanti Klingspor; Angelika Bondzio; Holger Martens; Jörg R. Aschenbach; Katharina Bratz; Karsten Tedin; Ralf Einspanier; Ulrike Lodemann (Mediators of Inflammation)
Probiotics have shown positive effects on gastrointestinal diseases; they have barrier-modulating effects and change the inflammatory response towards pathogens in studies in vitro. The aim of this investigation has been to examine the response of intestinal epithelial cells to Enterococcus faecium NCIMB 10415 (E. faecium), a probiotic positively affecting diarrhea incidence in piglets, and two pathogenic Escherichia coli (E. coli) strains, with specific focus on the probiotic modulation of the response to the pathogenic challenge. Porcine (IPEC-J2) and human (Caco-2) intestinal cells were incubated without bacteria (control), with E. faecium, with enteropathogenic (EPEC) or enterotoxigenic E. coli (ETEC) each alone or in combination with E. faecium. The ETEC strain decreased transepithelial resistance (TER) and increased IL-8 mRNA and protein expression in both cell lines compared with control cells, an effect that could be prevented by pre- and coincubation with E. faecium. Similar effects were observed for the increased expression of heat shock protein 70 in Caco-2 cells. When the cells were challenged by the EPEC strain, no such pattern of changes could be observed. The reduced decrease in TER and the reduction of the proinflammatory and stress response of enterocytes following pathogenic challenge indicate the protective effect of the probiotic.